OBTAINED IN CATTLE POISONING VETERINARY SANITARY EXAMINATION OF PRODUCTS - Dostkulov V. M.; Suyunov R. O.; Jumanazarov A.S.; Toshbekov I. A. (Journals Park Publishing, 2023)
This article describes the interpretation of the literature on the poisoning of cattle with pesticides, chloroorganic compounds with strongly acting substances, the elimination of products from infected animals from veterinary sanitary equipment.
Keywords: pesticides, chloroorganic compounds, phosphamide, utifos, chlorophos gastrointestinal tract, epicardium, endocardium, liver, kidney.